Eve in paradise and the nature of fault in Ambrose’s exegesis (Circe de clásicos y modernos, 2018)
Woman’s role has been largely discussed by the Fathers of the Church, particularly in connection with the initial fault, the Church’s conception of woman as human being and her influence in structure and meaning of society. This article analyzes the representation of woman and her involvement in the first sin in the treatise On paradise by Ambrose of Milan. We focus our analysis on the Bishop’s exegetical procedure that gives the work a structure and literary meaning, although it is a pastoral text, and links it with the philonic hermeneutical tradition.
Keywords: exegesis; paradise; Eve; sin; Ambrose of Milan